Perbandingan Hasil Tes Fisik Atlit Remaja Ditinjau dari Jenis Kelamin Laki-Laki dan Perempuan - Dody Tri Iwandana; Ardhika Falaahudin; Wildan Alfia Nugroho; Septa Ardiansyah; Muntaha Sururi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The purpose of this study was to compare the results of physical fitness tests among adolescent athletes based on gender (male and female). The population of this study consisted of 135 students enrolled in the Special Sports Class (KKO) at SMP Negeri 13 Yogyakarta. The research method employed was descriptive quantitative. Data were collected using physical condition test instruments, and the data analysis technique used descriptive percentage analysis. The results of the statistical analysis from various physical tests conducted on female and male groups showed differences in mean scores, group differences, and significance levels (p-values) as follows: (1) The Bleep Test showed that the mean score of the female group was 5.0372, while the male group scored higher at 8.1178, with a difference of -3.08058. The p-value of 0.002 indicates that this difference is statistically significant, meaning that males performed significantly better than females in this test. (2) The T-Test showed that the female group had a mean of 11.9130, slightly higher than males at 10.7727, with a difference of 1.14030; however, the p-value of 0.098 indicates that this difference was not statistically significant. (3) In the Push-Up test, the female mean was 28.3721, slightly lower than males at 29.1688, with a difference of -0.79674; the p-value of 0.676 indicates no significant difference. (4) The Sit-Up test showed that females had a mean of 41.6279, lower than males at 49.9221, with a difference of 8.29417; the p-value of 0.000 indicates a statistically significant difference. (5) In the Dynamic Balance test, females had a mean of 37.7907, lower than males at 47.8831, with a difference of 10.09242; the p-value of 0.000 indicates a significant difference. (6) The V-Sit and Reach test showed that females had a mean of 16.5116, higher than males at 14.1277, with a difference of 2.38397; however, the p-value of 0.058 indicates that this difference was not statistically significant. (7) The Standing Broad Jump test showed that females had a mean of 1.2635, nearly similar to males at 1.3074, with a difference of 0.17020; the p-value of 0.797 indicates no significant difference. (8) The Hand and Eye Coordination test showed that females had a mean of 19.3488, slightly higher than males at 18.0658, with a difference of 1.53882; the p-value of 0.406 indicates no significant difference. (9) The 30-meter Sprint test showed that females had a mean of 5.6212, higher than males at 5.0234, with a difference of 0.59778; the p-value of 0.451 indicates no significant difference. Based on the data analysis, it can be concluded that the comparison of physical fitness test results among adolescent athletes based on gender in the Special Sports Class (KKO) of SMP Negeri 13 Yogyakarta shows that there are several significant differences in physical abilities between male and female groups. Keywords: Athletes, Gender, Physical Fitness Test